‘The Standard-bearer of the Roman Church’: Lorenzo da Brindisi (1559-1619) and Capuchin Missions in the Holy Roman Empire - Drenas, A; Andrew Drenas (2014)
This thesis examines the missionary work of the Italian Capuchin Lorenzo da Brindisi. Renowned in his own day as a preacher, Bible scholar, missionary, chaplain, and diplomat, as well as vicar general of his Order, Lorenzo led the first organised, papally-commissioned Capuchin mission among the non-Catholics of Bohemia in the Holy Roman Empire from 1599 to 1602, and returned there, again under papal mandate, from 1606 to 1613. This thesis examines Lorenzo’s evangelistic and polemical activities in Central Europe in order to shed light on some of the ways the Capuchins laboured in religiously divided territories to confirm Catholics in their faith and to win over heretics. The introduction explains, principally, the thesis’s purpose and the historiographical background. Chapter one provides a brief biographical sketch of Lorenzo’s life followed by details of his afterlife. Chapter two examines his leading role in establishing the Capuchins’ new Commissariate of Bohemia-Austria-Styria in 1600, and specifically its first three friaries in Prague, Vienna, and Graz. Chapter three treats his preaching against heresy. Chapter four focuses on how Lorenzo, while in Prague, involved himself directly in theological disputations with two different Lutheran preachers. The first dispute, with Polykarp Leyser, took place in July 1607, and dealt with good works and justification. The second, with a Lutheran whose name is not known for certain, and which occurred in August 1610, concerned Catholic veneration of the Virgin Mary. Chapter five analyses the Lutheranismi hypotyposis, Lorenzo’s literary refutation of Lutheranism following additional contact with Polykarp Leyser in 1607. The conclusion considers briefly the effectiveness of Lorenzo’s apostolate and closes with a review of the thesis as a whole.